2021
DOI: 10.1037/adb0000679
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in daily life: Examining the role of trait and state impulsivity facets.

Abstract: Objectives: Using ecological momentary assessment (EMA) methods we aimed to investigate the influence of trait and state (momentary) impulsivity on alcohol use behaviors in daily life. Facets of the UPPS trait model of impulsivity (Whiteside & Lynam, 2001) have been found to differentially relate to alcohol-related outcomes and behaviors in cross-sectional and longitudinal studies. The present work expands on this by assessing UPPS facets in daily life and examining the contributions of trait and state impulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…More specifically, for participants who were at mean and high levels of sensation seeking and lack of premeditation, engaging in pregaming was associated with significant increases in the total amount of alcohol consumed on a given drinking day. These findings largely corroborate prior work demonstrating that premeditation, or a lack thereof, most strongly predicts alcohol use (e.g., Coskunpinar et al, 2013;Griffin & Trull, 2021) and interacts with drinking in a stimulating context to predict growth in drinking (Waddell, King, et al, 2022). Because pregame events occur prior to a later drinking episode (Zamboanga & Olthuis, 2016), it may be that individuals who have difficulty planning ahead (i.e., those who lack of premeditation) fail to account for future opportunities to drink, leading to higher consumption across both the pregame and later drinking events.…”
Section: Impulsive Pregamingsupporting
confidence: 87%
“…More specifically, for participants who were at mean and high levels of sensation seeking and lack of premeditation, engaging in pregaming was associated with significant increases in the total amount of alcohol consumed on a given drinking day. These findings largely corroborate prior work demonstrating that premeditation, or a lack thereof, most strongly predicts alcohol use (e.g., Coskunpinar et al, 2013;Griffin & Trull, 2021) and interacts with drinking in a stimulating context to predict growth in drinking (Waddell, King, et al, 2022). Because pregame events occur prior to a later drinking episode (Zamboanga & Olthuis, 2016), it may be that individuals who have difficulty planning ahead (i.e., those who lack of premeditation) fail to account for future opportunities to drink, leading to higher consumption across both the pregame and later drinking events.…”
Section: Impulsive Pregamingsupporting
confidence: 87%
“…Consequently, it is important to measure both trait and state impulsivity via self-report and behavioral measures over time to better understand the relationship to clinical outcomes in real-world settings [ 29 ]. The majority of trait and behavioral measures of impulsivity were not designed or validated as state measures or for use as part of a frequent monitoring assessment paradigm; however, several initial studies have revealed that impulsive behaviors can be reliably measured in real-world settings using ecological momentary assessment (EMA) and experience sampling [ 21 , 29 - 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Griffin (2018) examined momentary aspects of impulsivity (assessed via a four-item scale comprising components of impulsivity in the UPPS) and the relationship with alcohol use in the daily life of adults aged 18 to 45. The findings demonstrated that momentary reported lack of premeditation was a significant predictor of momentary drinking [44]. Similarly, Stamates et al (2019) found that within-subject variability in impulsivity measured through the momentary impulsivity scale (MIS) was positively associated with increased odds of heavy drinking in a sample of 24 young adults [24].…”
Section: State/momentary Impulsivity and Substance Usementioning
confidence: 90%